Multiplex detection of meningitis and encephalitis pathogens: A study from laboratory to clinic - Si, Yanjun; He, Weijun; Guo, Shuo; Wang, Xiaohui; Tang, Meng; Ying, Binwu; Wang, Minjin (Frontiers in Neurology, 2022)
Infectious meningitis and encephalitis (ME) are life-threatening conditions are caused by various pathogens. Conventional laboratory tests with low sensitivity and specificity cannot help with early diagnosis. Therefore, a prospective study using the novel multiplex PCR detection for 18 pathogens of ME (MME-18) was conducted to investigate the clinical utilization and the epidemiology characteristics of ME in southwestern China. Patients with suspected intracranial infection were recruited between May and October 2019 at West China Hospital of Sichuan University. The MME-18 was used to detect cerebrospinal fluid, and conventional experiments including cryptococcal capsular antigen detection, GeneXpert, real-time PCR, and clinical feedback were used to verify the result of MME-18. Among 581 tested patients, 139 eligible individuals were enrolled in the study. Among them, Mycobacterium tuberculosis was the most common pathogen in mono-infection. Viruses and Cryptococcus neoformans were also frequently detected. Of 139 infected patients, 12 cases were diagnosed by MME-18 only, 57 patients by conventional testing only, and 70 cases by both comparator tests and MME-18. There were 96.3% (79/82) diagnoses made by MME-18 had a favorable outcome, and two of twelve diagnoses, made solely by MME-18, had a likely unclear clinical significance. The MME-18 showed satisfactory consistency with expert clinical consensus for patients presenting with ME. Combined with conventional testing and clinical suspicion, MME-18 may help clinicians with the early identification of pathogens.